EVALUASI KEBERADAAN TROTOAR DI JALAN NASIONAL KOTA PONTIANAK - Rendra, Dede Gusti; Mayuni, Siti; Sulandari, Eti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
One of the impact of increased traffic flow resulting in increased traffic problems. The condition of the facility equipment can be used as one of the identification problem of traffic safety in the area. Good road conditions must be balanced with the presence of sidewalks available well too, so that the conflict - traffic can occur between motorists with pedestrians crossing the road can terhindar.Tujuan this study was to determine and evaluate the presence of sidewalks on seven National roads are there in the city of Pontianak. Data were collected by direct observation that the data obtained by direct observation. From a survey of geometric and pavement where the seven-dimensional data obtained by the National road pavement, pavement conditions, and land use. Referring to the results of the survey, taken two national roads which have the densest pedestrian volume that is considered to represent for the survey and the number of pedestrian travel time to get the value of current, velocity, density, space, and value the level of service that is on the road pavement Kom.Yos . Sudarso and the Tanjung Pura. Based on the analysis get LOS A service level pavement on both the road pavement which means that the service is still good enough to accommodate pedestrian flow across the pavement dijalur thus considered to represent the condition of seven other national roads. The survey results and the geometric conditions of the existence of national road pavement, the existing pavement is still not optimal as broken pavement condition, the dimensions are not standardized, the placement is not maximized, and the improper use of a sidewalk that needs improvement, reviewing, and controlling pavement in order to meet the standards and can provide maximum service to its users. Keywords: Evaluation, sidewalks, pedestrian level of service.